Pelatihan metacognitive memorizing model untuk penguatan pemahaman Bahasa Arab qur’ani bagi penghafal al-Qur’an berbasis chunking digital materials - Fauzi, Moh. Fery; Fauzan, Moh.; Anam, Faris Khoirul; Nada, Auqi Lu’lu In; Kinanthi, Keysha Wahyu; Anindiati, Irma (PERDIKAN (Journal of Community Engagement), 2024)
Teaching Qur’anic Arabic is often overlooked in programs for Qur’an memorization, even though it is essential for students to memorize and comprehend the divine message in its original language. Teaching Qur’anic Arabic has faced challenges in the digital era in many pesantren. They have faced numerous problems in media usage and teaching methods, especially for teachers who are teaching students specializing in Qur’an memorization. This community service programs aim to provide Metacognitive Memorizing Model Training to strengthen understanding of Qur’anic Arabic for Qur’anic memorizers based on Chunking Digital Materials. This community service activity was conducted at Pondok Pesantren Tahfizul Qur’an Al-Mu’anawiyah, Sambisari, Ceweng, Diwek, Jombang. This service activity was carried out in 5 phases, namely: (1) socialization of activities to partners; (2) assessment of technological pedagogical content knowledge (TPACK); (3) Focus Group Discussion (FGD) between the service team and the head of the foundation and pesantren administrators; (4) training in the application of the Metacognitive Memorizing Model to strengthen understanding of Qur’anic Arabic; and (5) mentoring. The results of this activity are that the community service team has developed Moodle-based e-learning for interactive Arabic language learning, written a book entitled ‘E-Learning Arabic Language Learning,’ and researched and published work related to Arabic Language Learning innovations. The level of technology readiness for the community service is at level 4, which is the application of the use, development, and application of technology in society. The result of this training activity is that the students of Al-Qur’an memorization have high enthusiasm for learning Arabic and can apply the Qur’anic Arabic Comprehension of Chunking Digital Materials method.[Pengajaran Bahasa Arab Qur’ani sering terabaikan dalam program-program hafalan Al-Qur’an, padahal hal ini sangat penting bagi siswa/santri tidak hanya untuk menghafal tetapi juga memahami pesan Ilahi dalam bahasa asli, yakni bahasa Arab. Pengajaran bahasa Arab Qur’ani menghadapi tantangan dan kendala di banyak pesantren. Mereka menghadapi berbagai masalah dalam penggunaan media dan metode pengajaran, terutama bagi para guru dalam mengajar siswa yang focus dalam menghafal Al-Qur’an. Pengabdian ini bertujuan untuk memberikan Pelatihan Metacognitive Memorizing Model untuk penguatan pemahaman Bahasa Arab Qur’ani bagi penghafal Al-Qur’an berbasis Chunking Digital Materials. Kegiatan pengabdian ini dilakukan di Pondok Pesantren Tahfizul Qur'an Al-Mu'anawiyah, Sambisari, Ceweng, Diwek, Jombang. Kegiatan pengabdian ini dilakukan dalam 5 fase, yaitu: (1) sosialisasi kegiatan kepada mitra; (2) pengkajian Technological Pedagogical Content Knowledge (TPACK); (3) Focus Group Discussion (FGD) antara tim pengabdian dengan ketua yayasan dan pengurus pesantren; (4) pelatihan penerapan Metacognitive Memorizing Model untuk penguatan pemahaman Bahasa Arab Qur’ani; dan (5) pendampingan. Keunggulan kegiatan ini adalah tim pengabdian telah mengembangkan e-learning berbasis moodle untuk pembelajaran Bahasa Arab interaktif dan menulis buku berjudul, “E-Learning Pembelajaran Bahasa Arab” serta meneliti dan memublikasikan karya terkait inovasi Pembelajaran Bahasa Arab (PBA). Tingkat Kesiapterapan Teknologi (TKT) pengabdian ini berada pada level 4, yaitu aplikasi penggunaan, pengembangan, dan penerapan teknologi di masyarakat. Hasil dari kegiatan pelatihan ini adalah santri penghafal Al-Qur'an memiliki antusias yang tinggi dalam belajar bahasa Arab dan mampu menerapkan pembelajaran bahasa Arab Qur'ani dengan media Chunking Digital Materials.]